NUMERICAL MODELING OF AN L – SHAPED VERY STIFF CONCRETE RETAINING WALL (Sciences & Technologie. B, Sciences de l'ingénieur, 2005)
A numerical model developed using the finite element Plaxis program is presented in this paper tosimulate the behaviour of a stiff “L” shaped retaining wall supporting sand. For validating theproposed numerical model, reference was made to an experimental model tested in a centrifugeexperiment. The proposed numerical model intended to predict the behaviour of a target prototypeand to check the validity of the modelling concept used. Taking into account the geometry anddimensions of the wall with respect to the centrifuge scaling law, the loading conditions andconsidering the hardening soil model, it was found that the predicted pattern and magnitude of thewall displacements were close to the experimentally observed results. A good agreement between themeasured and the numerically computed lateral pressures acting on the wall stem was also obtainedwith comparison to the classical approach.